2021
DOI: 10.1021/acs.jchemed.1c00714
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Signals from Automaticity Diagnostic Instruments for First- and Second-Semester General Chemistry

Abstract: The Math-Up Skills Tests (MUST) has been used in multiple research projects conducted by the Networking for Science Advancement (NSA) team to determine how automaticity skills (what can be done without a calculator) in arithmetic can be used to predict if students will be successful (course average = 69.5%+) in general chemistry. This study expands our investigations to include how students’ quantitative literacy/quantitative reasoning (QL/QR) abilities influence their success. The NSA team studied multiple cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The opposite was true for students with lower math placement exam scores. Again, after controlling for IC course grade, students who placed into a course below calculus were less likely to complete GC-I, agreeing with the literature on a link between chemistry performance and math aptitude. …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The opposite was true for students with lower math placement exam scores. Again, after controlling for IC course grade, students who placed into a course below calculus were less likely to complete GC-I, agreeing with the literature on a link between chemistry performance and math aptitude. …”
Section: Discussionsupporting
confidence: 71%
“…Beyond differences in performance between demographic groups, grades and achievement in general chemistry have also long been related to students’ mathematics aptitude. In particular, SAT and ACT math scores have been found to correlate highly with success in chemistry, ,, and performance on university developed and validated presemester assessments have corroborated these results. As such, placing students into the appropriate chemistry course and bridging the gap between mathematically underprepared and prepared students are a challenge for chemical educators. Some institutions require a mathematics prerequisite, provide supplemental corequisite offerings that accompany mainstream courses, or have created distinct course pathways for students of varying preparedness based on their academic needs. ,,,− …”
Section: Review Of the Literaturementioning
confidence: 99%
“…Many of these include the mathematics portion of the SAT or ACT (Craney and Armstrong, 1985;Rixse and Pickering, 1985;Spencer, 1996;Lewis and Lewis, 2007;Ralph and Lewis, 2018;Kreiser et al, 2022), while others are more institution-based and cover common topics. Logarithms, scientific notation, graphs, algebra, and arithmetic without the use of a calculator frequently appear on these assessments of quantitative literacy and quantitative reasoning (Bohning, 1982;Leopold and Edgar, 2008;Kennepohl et al, 2010;Shelton et al, 2021). Tai et al (2006) identified multiple significant mathematicsrelated predictor variables in a regression model for success in first-semester college chemistry; these included enrollment in calculus in high school, SAT-math score, last grade in a high school mathematics course, and experience with stoichiometry in high school chemistry.…”
Section: Mathematics Assessments and Chemistry Coursesmentioning
confidence: 99%